THE DOUBLE WISHBONE SUSPENSION DESIGN OF THE GAJAH OLING ELECTRIC VEHICLE (DINAMIS, 2024)
The ongoing development of electric vehicles is aimed at swapping conventional fossil fuel-powered automobiles, namely those reliant on petrol and diesel. In order to achieve optimal use in practical scenarios, electric vehicles must possess the capability to navigate diverse terrain elements. The utilization of suspension systems serves the objective of reducing the magnitude of the load exerted on the tires, hence facilitating enhanced driver control over the electric vehicle. The spring performance of the suspension system in an electric car design is evaluated for different weight configurations. Specifically, when the car weight 120.4 Kg, the suspension exhibits a spring constant of 59.0N/m. Similarly, when the weight is 115.4 Kg, the suspension system demonstrates a spring constant of 62.8N/m. Finally, in the front suspension configuration with a weight of 129.4 Kg, the spring constant is measured to be 57.7 N/m. The constant data have been aggregated to determine that the maximum load capacity of the suspension system under shock conditions is 365.8 kg. Based on the findings of the design results, it was seen that the highest damping constant was recorded in the case of a load weighing 120.4 Kg, specifically in the low mode with a value of 285.41 Ns/m, and in the mid mode with a value of 196.6 Ns/m.